Developing a Signature Pedagogy in Master’s Research Training - Maribeth F Jorgensen; Lindsey K Umstead (Teaching and Supervision in Counseling, 2020)
Signature pedagogies have been identified as a conduit for unifying programs and socializing professionals to have similar values, skills, knowledge, and practices. Recently, Baltrinic and Wachter Morris (in press) put out a call to counselor educators to reflect on and consider signature pedagogies. Signature pedagogies in counselor education have been minimally explored and based on findings of empirical studies, there appears to be variability in some areas of preparation such as research training at the master’s level. In this article, we join in the dialogue about signature pedagogies in counselor education by discussing research training at the master’s level. We also provide a framework for initial steps toward developing a signature pedagogy in this domain and suggestions for empirical exploration.
Keywords: master’s-level research training; counselor research preparation; signature pedagogy in research